2015
DOI: 10.1038/tpj.2015.25
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B*59:01: a marker for Stevens–Johnson syndrome/toxic epidermal necrolysis caused by methazolamide in Han Chinese

Abstract: Methazolamide is an intraocular pressure-lowering drug that is used in the treatment of glaucoma and other ophthalmologic abnormalities. The use of methazolamide has been shown to cause Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) in patients of Asian ancestry. Methazolamide-induced SJS/TEN is associated with the presence of HLA-B59 serotype/HLA-B*59:01 in Korean and Japanese populations. To better understand the genetic risk factors for these adverse reactions in the Han Chinese populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…In terms of HLA-A*31:01 (IMGT/HLA ID: HLA00097) allele which associates with CBZ-induced CADRs, neither the frequencies within Thailand nor among different populations were significantly different ( Tables 7, 8A). HLA-B*58:01 (IMGT/HLA ID: HLA00386) allele was similarly distributed in Thais (6.38%), African Americans (6.37%), and Asians (7.38%) (Yang et al, 2016) and higher than those reported in Caucasians (Cao et al, 2001), Hispanics (Cao et al, 2001), and North Americans (Cao et al, 2001) ( Tables 7, 8A). However, HLA-B*58:01 allele was not significantly different across different populations.…”
Section: Distribution Of Pharmacogenetics Markersmentioning
confidence: 90%
“…In terms of HLA-A*31:01 (IMGT/HLA ID: HLA00097) allele which associates with CBZ-induced CADRs, neither the frequencies within Thailand nor among different populations were significantly different ( Tables 7, 8A). HLA-B*58:01 (IMGT/HLA ID: HLA00386) allele was similarly distributed in Thais (6.38%), African Americans (6.37%), and Asians (7.38%) (Yang et al, 2016) and higher than those reported in Caucasians (Cao et al, 2001), Hispanics (Cao et al, 2001), and North Americans (Cao et al, 2001) ( Tables 7, 8A). However, HLA-B*58:01 allele was not significantly different across different populations.…”
Section: Distribution Of Pharmacogenetics Markersmentioning
confidence: 90%
“…reported that HLA‐B*59:01 was strongly linked with methazolamide‐induced SJS/TEN in both the Japanese and Korean populations. Yang et al . also demonstrated a similar association in eight Han Chinese patients.…”
mentioning
confidence: 59%
“…Methazolamide, a sulfonamide derivative, is indicated in the treatment of glaucoma. Several case reports of methazolamide‐induced SJS/TEN have primarily been reported in the context of HLA‐B59 in the Japanese, Korean, and Chinese populations . A correlation between HLA‐B59 and methazolamide‐induced SJS/TEN was initially suggested in a Japanese patient in 1997 .…”
mentioning
confidence: 99%
“…Methazolamide is a carbonic anhydrase inhibitor used to treat glaucoma. It has been reported to be associated with SJS/TEN in Han Chinese patients (Yang et al ., ). The study reported associations with the haplotype HLA‐B*59:01‐HLA‐C*01:02.…”
Section: Resultsmentioning
confidence: 97%